The Prospective Position of Nuclear Power in Turkish Energy Policy - Biresselioglu, Mehmet Efe (Richtmann Publishing, 2012)
Energy security is one of the key challenges confronting the nations all around the globe. Diversification of imports in terms ofsources, route, resources and technologies has been an important policy tool to advance energy security further. Geographically locatedin close proximity to fossil fuel rich regions, Turkey has connected itself to producer countries via several pipelines with the aim ofbecoming a transit hub. At the same time, however, Turkey became increasingly dependent to foreign imports, reaching 70 per cent. Asa result, Turkey moved towards nuclear energy and signed a deal with Russia to build its first nuclear power plant. The recent globaladvances in nuclear power generation enhanced the importance of nuclear power in bridging the energy gap in Turkey. Nuclear energyis currently enjoying enormous interest internationally, and particularly in Turkey, due to a combination of factors such as increasing fuelprices, diminishing resources of the fossil fuels, and environmental problems. On the other hand, by signing a deal with Russia, whichalready provides a significant amount of Turkey’s imported energy, creates dangers of over-dependence on its neighbor. Moreover,there is a greater awareness of safety problems related to nuclear power plants after the recent incident in Japan, together withenvironmental concerns related to nuclear waste management, potentially threatening human security. Therefore, this article analysesTurkey’s nuclear energy interests and discusses in detail the advantages and disadvantages of enhancing the role of nuclear power forTurkey’s energy needs.